2019
DOI: 10.1093/jmcb/mjz099
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of ezrin regulates membrane–cytoskeleton interaction underlying CCL18-elicited cell migration

Abstract: Abstract Ezrin, a membrane–cytoskeleton linker protein, plays an essential role in cell polarity establishment, cell migration, and division. Recent studies show that ezrin phosphorylation regulates breast cancer metastasis by promoting cancer cell survivor and promotes intrahepatic metastasis via cell migration. However, it was less characterized whether there are additional post-translational modifications and/or post-translational crosstalks on ezrin underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Binding to specific interaction partners might contribute to ERM-1 localization, but alternative mechanisms of regulation are also possible. For example, a recent study found that in breast epithelial cells, ezrin membrane association is regulated by acetylation of ezrin (Song et al, 2019). Overall, these results demonstrate that C-terminal phosphorylation is a versatile regulatory modification that modulates ERM-1 function in a context-dependent manner and underscore the importance of studying ERM regulation in different biological scenarios.…”
Section: Discussionmentioning
confidence: 60%
“…Binding to specific interaction partners might contribute to ERM-1 localization, but alternative mechanisms of regulation are also possible. For example, a recent study found that in breast epithelial cells, ezrin membrane association is regulated by acetylation of ezrin (Song et al, 2019). Overall, these results demonstrate that C-terminal phosphorylation is a versatile regulatory modification that modulates ERM-1 function in a context-dependent manner and underscore the importance of studying ERM regulation in different biological scenarios.…”
Section: Discussionmentioning
confidence: 60%
“…Identification of HCC migration inhibitors using natural products from Chinese herbs. Recent study unraveled the importance of ezrin protein acetylation in CCL18-elicited breast cancer metastasis 32 . Since our early study revealed the role of ezrin Thr567 phosphorylation in promoting intra-hepatocellular metastasis in xenografts and ezrin T567 phosphorylation in a context-dependent manner 20 , we sought to screen inhibitors to prevent the intra-hepatocellular carcinoma metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that ezrin and its interaction partner ACAP4 acetylation is involved in breast cancer metastasis in response to cytokine CCL18 stimulation 32,58 . Given the hyper-activation of Aurora kinase activity in HCC 59 , acetyl-phosphorylation cross-talk on the regulation of cellular dynamics 60 , it would be of great interest to delineate the spatiotemporal dynamics of ezrin acetylation and ROCK2-mediated phosphorylation in HCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In addition to the fact that αvβ3 directly enhances PCa invasion via chemokine-mediated processes, membrane dynamics are also involved in the migration of malignant tumors induced by chemokines. [63][64][65] Integrin αvβ3 directly interacts with the ECM. In addition, actin rearrangement also plays a key role in regulating cellular interactions with the ECM, such as motility and vesicular trafficking.…”
Section: Cellular Chemokines Can Enhance Pca Invasion By Regulating αmentioning
confidence: 99%